Comparative study on energy management and efficiency category in sustainable building rating schemes - Mohammed Usman, Abdullahi; Abdullah, Kamil; Batcha, Mohd Faizal Mohideen (Akademia Baru, 2018)
The paper aims to provide comparative study on energy management and efficiency category in sustainable building rating schemes. Eleven sustainable rating schemes have been considered in the present papers which consist of forty three tools. All the tools have been reviewed in terms of credits allocation, parameters allocation, and its credits requirement associated with energy management and efficiency category. In terms of credits allocation, all considered schemes have allocated at least ninety eight credits for parameters in energy management and efficiency category with minimum of twenty nine parameters. In addition to the credit and parameters allocation, the present work also provides specific requirement on the credits for each of the schemes. Eighty six parameters have been recognized from the tools associated to be associated with energy management and efficiency. All these parameters have been consolidated into eighteen parameters and would be very useful for the future development of the sustainable tools.